Tough bio-based nano composite material and preparation method thereof
By blending ethyl cellulose with polyvinylpyrrolidone and adding SiO2 hybrid nanoparticles, a tough biomass nanocomposite material was prepared, which solved the problem of comprehensive improvement of existing materials' performance and realized multiple biomass composite materials with excellent performance, suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411956709.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-03-28
AI Technical Summary
Existing biomass composite film materials are difficult to simultaneously improve their performances such as mechanical strength, ductility, hydrophobicity, ultraviolet barrier, antibacterial and ammonia-sensitive discoloration, which limits their application in food packaging, smart materials, antibacterial materials, ultraviolet protection, ammonia detection and other fields.
A tough bio-based nanocomposite material was prepared by blending ethyl cellulose with polyvinylpyrrolidone and adding SiO2 hybrid nanoparticles. The method of preparing the material includes stirring and drying ethyl cellulose, polyvinylpyrrolidone and SiO2 hybrid nanoparticles in ethanol to form a composite material with excellent properties.
The tough bio-based nanocomposite has excellent mechanical strength, ductility, hydrophobicity, ultraviolet barrier, antibacterial and ammonia-sensitive discoloration properties. Its preparation process is simple, environmentally friendly, and low-cost, and is suitable for a variety of application fields.
Smart Images

Figure CN119708645A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a strong and tough bio-based nano-composite material and a preparation method thereof. Background Art
[0002] In recent years, non-biodegradable, petroleum-based plastic products have caused great harm to the environment and also consumed a large amount of petroleum resources. Therefore, people have gradually turned their attention to the research of biodegradable and environmentally friendly bio-based materials. As an important bio-based material, ethyl cellulose is a water-insoluble cellulose derivative. Due to its unique naturalness, biocompatibility and biodegradability, it has been widely used in the food and pharmaceutical industries. However, ethyl cellulose film materials have good optical transparency, but their UV blocking properties are poor, which is not conducive to their application in food packaging, UV protection and other fields. Polyvinyl pyrrolidone is a non-ionic polymer compound with good solubility, film-forming properties, UV absorption capacity, physiological compatibility, biodegradability and other characteristics. It is widely used in medicine, food, cosmetics and other fields. Ethyl cellulose and polyvinyl pyrrolidone are blended to obtain ethyl cellulose / polyvinyl pyrrolidone composite film materials that combine the advantages of ethyl cellulose and polyvinyl pyrrolidone, so that it is expected to develop excellent bio-based composite materials and broaden their application fields. As an inorganic material, SiO2 nanoparticles have good biocompatibility and chemical stability, and have high specific surface area and small size, which makes them have excellent surface activity and adjustable physical and chemical properties, so that they have broad application prospects in many fields such as enhancement and modification of bio-based composite materials, biomedicine, optoelectronic devices, catalysts, etc. At present, many studies have reported the enhancement and modification of bio-based composite membrane materials such as ethyl cellulose by using SiO2 nanoparticles, but few studies have reported how to simultaneously improve the mechanical strength, ductility, hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change properties and functions of composite membrane materials. Therefore, how to effectively develop strong and tough bio-based nanocomposites with excellent mechanical strength, ductility, hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change properties, so as to be suitable for food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety, etc., is a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a strong and tough bio-based nanocomposite material and a preparation method thereof. The strong and tough bio-based nanocomposite material has excellent mechanical strength, ductility, hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, suitable for scale-up production, and is suitable for food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields.
[0004] Technical solution of the present invention:
[0005] The present invention provides a strong and tough bio-based nanocomposite material, characterized in that it is composed of the following components in parts by weight: 90 parts of ethyl cellulose, 10 parts of polyvinyl pyrrolidone, and 3-9 parts of SiO2 hybrid nanoparticles;
[0006] The preparation method of the SiO2 hybrid nanoparticles comprises the following steps:
[0007] (1) Take 9.72 parts of ferulic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform ferulic acid solution for later use;
[0008] (2) Disperse 30 parts of nano-SiO2 in 1000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform SiO2 dispersion for later use;
[0009] (3) adding the nano-SiO2 dispersion obtained in step (2) to the ferulic acid solution obtained in step (1), stirring at room temperature for 50 min to obtain a uniform mixed solution for later use;
[0010] (4) Take 13.91 parts of ferrous sulfate heptahydrate and dissolve it in 1000 parts of deionized water to obtain a uniform ferrous sulfate solution for later use;
[0011] (5) Add the ferrous sulfate solution obtained in step (4) to the mixed solution obtained in step (3), stir and react at room temperature for 20 min, then centrifuge, wash and dry in sequence to obtain SiO2 hybrid nanoparticles.
[0012] The present invention also provides a method for preparing the above-mentioned strong and tough bio-based nanocomposite material, which is characterized by comprising the following steps:
[0013] (1) Add 90 parts of ethyl cellulose and 10 parts of polyvinyl pyrrolidone to 3000 parts of ethanol, stir at room temperature for 30 min, and then stir at 50°C for 30 min to obtain a uniform blend solution for later use;
[0014] (2) dispersing 3-9 parts of SiO2 hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use;
[0015] (3) Add the dispersion obtained in step (2) to the blended solution obtained in step (1), and stir at 50° C. for 30 min to obtain a uniform film-forming solution for later use;
[0016] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55°C for 24 hours to obtain a strong and tough bio-based nanocomposite material.
[0017] The application of the strong and tough bio-based nanocomposite material is characterized by being used in the fields of food packaging, smart materials, antibacterial materials, ultraviolet protection, ammonia detection, environmental monitoring and safety.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The strong and tough bio-based nanocomposite material prepared by the present invention has excellent mechanical strength, ductility, hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has wide application value in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a scanning electron microscope image of the SiO2 hybrid nanoparticles involved in the present invention;
[0021] Figure 2 These are actual photos of the ethyl cellulose / polyvinyl pyrrolidone composite material prepared in Comparative Example 1 and the tough bio-based nanocomposite material samples prepared in Example. DETAILED DESCRIPTION
[0022] The present invention is described in detail below through examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the contents of the present invention. The parts of the raw materials are all parts by weight unless otherwise specified.
[0023] In the following specific embodiments and comparative example formulas and preparation methods, the ethyl cellulose used is a product provided by McLean Biochemical Technology Co., Ltd. (CAS No.: 9004-57-3); nano-SiO2 (i.e., nano-silicon dioxide) is a product provided by Shanghai Aladdin Biochemical Technology Co., Ltd. (Article No.: S104596-100g, 99.5% metals basis, particle size of 30nm); polyvinyl pyrrolidone (Article No.: R018594-500g) and ferulic acid are analytically pure reagents provided by Shanghai Yien Chemical Technology Co., Ltd.; ferrous sulfate heptahydrate is an analytically pure reagent provided by Xilong Science Co., Ltd.
[0024] In the following specific embodiments and comparative examples, the preparation method, the preparation method of the SiO2 hybrid nanoparticles comprises the following steps:
[0025] (1) Take 9.72 parts of ferulic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform ferulic acid solution for later use;
[0026] (2) Disperse 30 parts of nano-SiO2 in 1000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform SiO2 dispersion for later use;
[0027] (3) adding the nano-SiO2 dispersion obtained in step (2) to the ferulic acid solution obtained in step (1), stirring at room temperature for 50 min to obtain a uniform mixed solution for later use;
[0028] (4) Take 13.91 parts of ferrous sulfate heptahydrate and dissolve it in 1000 parts of deionized water to obtain a uniform ferrous sulfate solution for later use;
[0029] (5) Add the ferrous sulfate solution obtained in step (4) to the mixed solution obtained in step (3), stir and react at room temperature for 20 min, then centrifuge, wash and dry in sequence to obtain SiO2 hybrid nanoparticles.
[0030] Example 1
[0031] A strong and tough bio-based nano-composite material, characterized in that it is composed of the following components in parts by weight: 90 parts of ethyl cellulose, 10 parts of polyvinyl pyrrolidone, and 3 parts of SiO2 hybrid nanoparticles.
[0032] The preparation method comprises the following steps:
[0033] (1) Add 90 parts of ethyl cellulose and 10 parts of polyvinyl pyrrolidone to 3000 parts of ethanol, stir at room temperature for 30 min, and then stir at 50°C for 30 min to obtain a uniform blend solution for later use;
[0034] (2) dispersing 3 parts of SiO2 hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use;
[0035] (3) Add the dispersion obtained in step (2) to the blended solution obtained in step (1), and stir at 50° C. for 30 min to obtain a uniform film-forming solution for later use;
[0036] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55°C for 24 hours to obtain a strong and tough bio-based nanocomposite material.
[0037] Example 2
[0038] A strong and tough bio-based nano-composite material, characterized in that it is composed of the following components in parts by weight: 90 parts of ethyl cellulose, 10 parts of polyvinyl pyrrolidone, and 6 parts of SiO2 hybrid nanoparticles.
[0039] The preparation method comprises the following steps:
[0040] (1) Add 90 parts of ethyl cellulose and 10 parts of polyvinyl pyrrolidone to 3000 parts of ethanol, stir at room temperature for 30 minutes, and then stir at 55°C for 30 minutes to obtain a uniform blend solution for later use;
[0041] (2) dispersing 6 parts of SiO2 hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use;
[0042] (3) Add the dispersion obtained in step (2) to the blended solution obtained in step (1), and stir at 50° C. for 30 min to obtain a uniform film-forming solution for later use;
[0043] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55°C for 24 hours to obtain a strong and tough bio-based nanocomposite material.
[0044] Example 3
[0045] A strong and tough bio-based nano-composite material, characterized in that it is composed of the following components in parts by weight: 90 parts of ethyl cellulose, 10 parts of polyvinyl pyrrolidone, and 9 parts of SiO2 hybrid nanoparticles.
[0046] The preparation method comprises the following steps:
[0047] (1) Add 90 parts of ethyl cellulose and 10 parts of polyvinyl pyrrolidone to 3000 parts of ethanol, stir at room temperature for 30 min, and then stir at 50°C for 30 min to obtain a uniform blend solution for later use;
[0048] (2) dispersing 9 parts of SiO2 hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use;
[0049] (3) Add the dispersion obtained in step (2) to the blended solution obtained in step (1), and stir at 50° C. for 30 min to obtain a uniform film-forming solution for later use;
[0050] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55°C for 24 hours to obtain a strong and tough bio-based nanocomposite material.
[0051] Comparative Example
[0052] As a comparison standard of the above embodiments, the present invention provides an ethyl cellulose / polyvinyl pyrrolidone composite material prepared without SiO2 hybrid nanoparticles, comprising the following steps:
[0053] (1) Add 90 parts of ethyl cellulose and 10 parts of polyvinyl pyrrolidone to 3000 parts of ethanol, stir at room temperature for 30 min, and then stir at 50°C for 30 min to obtain a uniform blend solution for later use;
[0054] (2) Add 500 parts of ethanol to the blended solution obtained in step (1), and stir at 50° C. for 30 min to obtain a uniform film-forming solution for later use;
[0055] (3) The film-forming solution obtained in step (2) was poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain an ethyl cellulose / polyvinyl pyrrolidone composite material.
[0056] Structure and performance test:
[0057] The performance tests were conducted on the ethyl cellulose / polyvinyl pyrrolidone composite material prepared in the above comparative example and the tough bio-based nanocomposite material prepared in the example, wherein the UV-visible performance was tested by UV-visible spectrometer, and the average UV transmittance was calculated with reference to GB / T 18830-2009; hydrophobicity characterization: the water contact angle of the sample material was measured by a static contact angle tester; the tensile properties were tested by an electronic tensile testing machine (LDW-2G); the antibacterial property of the material was tested in accordance with QBT25912003; the ammonia response test method was as follows: the sample material was exposed to an ammonia environment for 15 minutes, the color change of the sample material was observed and recorded, and the color difference value ∆E of the sample material before and after the ammonia response was calculated (Note: ∆E >3 indicates an obvious color change visible to the human eye).
[0058] The above performance test data is shown in Table 1.
[0059] Table 1 Sample performance test data
[0060]
[0061] The results of the ammonia response test experiment show that the ethyl cellulose / polyvinyl pyrrolidone composite material prepared in the comparative example is colorless and transparent. After being exposed to an ammonia environment for 15 minutes, its color does not change, and it still exhibits colorless and transparent optical properties, and its ∆E value is 0.19 (that is, the color difference is negligible and cannot be distinguished by the human eye). The tough bio-based nanocomposite material prepared in Example 3 is yellow. After being exposed to an ammonia environment for 15 minutes, its color changes significantly (from yellow to brown), and its ∆E value is as high as 11.52 (Note: ∆E >3 indicates a significant color change visible to the human eye).
[0062] The results of the antibacterial test experiments show that the ethyl cellulose / polyvinyl pyrrolidone composite material prepared in the comparative example does not show obvious antibacterial activity against Escherichia coli and Staphylococcus aureus, while the strong and tough bio-based nano-composite material prepared in Example 3 has an inhibition rate of more than 99% against Escherichia coli and Staphylococcus aureus, that is, the strong and tough bio-based nano-composite material prepared in the example has excellent antibacterial activity.
[0063] In summary, it can be seen from the sample performance test data (see Table 1) that the strong and tough bio-based nanocomposite material prepared by the present invention has excellent mechanical strength, tensile elongation at break (i.e. ductility), hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has wide application value in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields.
[0064] The content of the present invention is not limited to the embodiments listed, and any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the description of the present invention are covered by the claims of the present invention.
Claims
1. A strong and tough bio-based nanocomposite material, characterized in that: The invention is composed of the following components in parts by weight: 90 parts of ethyl cellulose, 10 parts of polyvinyl pyrrolidone, and 3-9 parts of SiO2 hybrid nanoparticles; The preparation method of the SiO2 hybrid nanoparticles comprises the following steps: (1) Take 9.72 parts of ferulic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform ferulic acid solution for later use; (2) Disperse 30 parts of nano-SiO2 in 1000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform SiO2 dispersion for later use; (3) adding the nano-SiO2 dispersion obtained in step (2) to the ferulic acid solution obtained in step (1), stirring at room temperature for 50 min to obtain a uniform mixed solution for later use; (4) Take 13.91 parts of ferrous sulfate heptahydrate and dissolve it in 1000 parts of deionized water to obtain a uniform ferrous sulfate solution for later use; (5) Add the ferrous sulfate solution obtained in step (4) to the mixed solution obtained in step (3), stir and react at room temperature for 20 min, then centrifuge, wash and dry in sequence to obtain SiO2 hybrid nanoparticles.
2. The method for preparing a strong bio-based nanocomposite material according to claim 1, characterized in that The steps include: (1) Add 90 parts of ethyl cellulose and 10 parts of polyvinyl pyrrolidone to 3000 parts of ethanol, stir at room temperature for 30 minutes, and then stir at 50°C for 30 minutes to obtain a uniform blend solution for later use; (2) dispersing 3-9 parts of SiO2 hybrid nanoparticles in 500 parts of ethanol to obtain a uniform dispersion for later use; (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at 50° C. for 30 min to obtain a uniform film-forming solution for later use; (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55°C for 24 hours to obtain a strong and tough bio-based nanocomposite material.
3. The use of a tough bio-based nanocomposite material according to claim 1, characterized in that: Used in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety fields.